2021
DOI: 10.1021/acsami.0c20099
|View full text |Cite
|
Sign up to set email alerts
|

From Dendrites to Hemispheres: Changing Lithium Deposition by Highly Ordered Charge Transfer Channels

Abstract: Metallic lithium as an anode is an ultimate ideal for rechargeable lithium batteries with high energy density such as lithium–oxygen batteries and lithium–sulfur batteries. However, the excess reactivity and asymmetrical dissolution–deposition of the metallic lithium anode make it impossible to support a stable long charge–discharge cycling. To protect the metallic lithium anode, apparently it needs to adjust the dissolution and deposition of lithium ions, but more essentially, it should reasonably change the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Apparently, this is caused by lithium partially reducing Al 2 O 3 at the interface of both. 1,56 The F 1s spectrum of the lithium electrode and the Li 1s spectrum of GPE-ZIF8-Al 2 O 3 after being cycled are actually very complicated because these spectra could contain the signals of organic salt besides LiF and AlF 3 . However, from the C 1s spectrum of the lithium electrode, it can be found that C−F, CO, C−O, C−H, and C−C bonds appear in the surface of lithium after cycling.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Apparently, this is caused by lithium partially reducing Al 2 O 3 at the interface of both. 1,56 The F 1s spectrum of the lithium electrode and the Li 1s spectrum of GPE-ZIF8-Al 2 O 3 after being cycled are actually very complicated because these spectra could contain the signals of organic salt besides LiF and AlF 3 . However, from the C 1s spectrum of the lithium electrode, it can be found that C−F, CO, C−O, C−H, and C−C bonds appear in the surface of lithium after cycling.…”
mentioning
confidence: 99%
“…Metallic lithium has attracted extensive research attention as a promising anode material for rechargeable lithium–metal batteries (RLBs) with a large theoretical specific capacity of 3860 mAh g –1 and low reduction potential (−3.04 V vs standard hydrogen electrode). It is expected to build RLBs with high energy and power density to meet the increasing demands of future electronic equipment and electric vehicles. However, the lithium anode tends to trigger parasite reactions with the traditional organic liquid electrolyte due to its excessive reaction activity during the charge/discharge process .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[31][32][33] At present, the presence of SEI has been detected on the surface of several common anode materials such as metal lithium, [34,35] graphite [36] and silicon. [37][38][39] Figure 3a shows the relative electron energies of the anode, electrolyte and cathode for the thermodynamically stable redox pair in the LIBs. [40] If the electrochemical potentials of the anode (μA) are higher than the lowest unoccupied molecular orbital (LUMO) energy or the electrochemical potentials of the cathode (μC) are lower than the highest occupied molecular orbital (HOMO) energy, the electrode materials will undergo a redox reaction with the electrolyte to form SEI.…”
Section: The System Degradation Of Lfp-based Libmentioning
confidence: 99%
“…Utilizing the porous composite electrode with large specic surface areas, 15,16 increasing lithium deposition sites and reducing current density could realize the uniform lithium deposition, but the volumetric energy density of the electrode is sacriced, and large specic surface area will lead to more side reactions. Besides, protective coating layers composed of polymers, [17][18][19][20] inorganic materials [21][22][23] and their mixtures [24][25][26][27] are applied to suppress the lithium dendrites and improve the brittleness of SEI, but the transport kinetics of lithium ions in the modied layer still needs to be increased to alleviate the space charge layer. Therefore, it is essential to construct fast ion transport channels in the protective coating layer to ensure the rapid transport of lithium ions particularly.…”
Section: Introductionmentioning
confidence: 99%